FAKTOR PENENTU STRUKTUR PERMODALAN PERUSAHAAN BUMN PUBLIK DI BURSA EFEK INDONESIA PADA PASAR NEGARA BERKEMBANG PERIODE 2008-2016 - M. Iskandar Zulkarnaen A. (CALYPTRA, 2018)
This study examines the key determinants of Capital Structure in public-owned companies (BUMN) that listed on Indonesia Stock Exchange (BEI). Focuses on the ratio of short term debt and long term debt as the dependent variable. Growth, Liquidity, Profitability, Size, Tangibility, and Risk as an independent variable for the period of 2008-2016. This research use regression method in the form of panel data. The amount of data used in the observation are 144. Contains 16 public-owned companies except financial and banking sector industries during the period of 2018-2016. The result from this research shows that Growth and Risk has a significantly positive influence to the Capital Structure of BUMN. Liquidity, Profitability, and Size variables has a significantly negative influence to the Capital Structure of BUMN. Besides, Tangibility giving unsignificantly negative influence to the Capital Structure of BUMN.